POLITENESS IN THE LIMELIGHT: A CASE STUDY OF CHARLIE PUTH’S INTERVIEW ON “THE ELLEN SHOW” - Ilmi, Assayyidah Bil Ichromatil (PARADIGM: Journal of Language and Literary Studies, 2023)
This study aims to identify the politeness strategies present in the highly popular US show, The Ellen Show, where Charlie Puth appeared as a guest star. The research utilized qualitative methods, focusing on audio-visual data from The Ellen Show's YouTube channel. The analysis focused on two aspects: the politeness strategies used by the interviewer (Ellen) and those employed by the guest star (Charlie Puth). The findings of the study indicate a significant difference in the politeness strategies used by the host and the guest star. Ellen, as the presenter, predominantly utilized "bald on-record" and "negative politeness" strategies. On the other hand, Charlie Puth tended to employ "positive politeness" and "off-record" strategies more frequently. The results highlight that the variation in politeness strategies is influenced by social variables in the conversation and the relationship dynamics between the presenter and the guest star. This research had proven that the interview pattern used by Ellen as a host is different from other talk shows. Generally, interviewers will give the role of a speaker who has lower power than a guest star. However, the research results obtained were the result of interviewers who had different characteristics because the interviewers ignored the interview rules, which aimed to make the guest stars comfortable.